(Z)-3-Benzyl-2-[(2-phenylcyclohex-2-enyl)imino]-1,3-thiazolidin-4-one - Ooi, Chin Wei (International Union of Crystallography, 2012)
The title compound, C(22)H(22)N(2)OS, exists in a Z configuration with respect to the N=C bond. The cyclohexene ring adopts a distorted sofa conformation. The thiazolidine ring is essentially planar, with a maximum deviation of 0.030 (2) Å, and forms dihedral angles of 76.66 (6) and 74.55 (6)° with the terminal phenyl rings. The dihedral angle between the phenyl rings is 71.55 (7)°. In the crystal, a C—H⋯π interaction is observed.